Alluvial Zones of Decolonizing Internationalization of Higher Education - Lin, Gloria Y. (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2023)
Universities play a critical role in the “alluvial mixing” of Indigenous and Western knowledges, but at the same time they are reluctant to dismantle structures that support their ongoing epistemic ignorance, epistemic biases, and epistemic dominance and are resistant to dismantle hierarchies that maintain the status quo (Marker, 2019). Decolonization and internationalization of higher education does not exist in separate realities, but exists in alluvial third spaces that are often turbulent, contested, and contradictory. This article encourages researchers, faculty, and staff to rethink assumptions about long-standing, deeply-rooted policies, practices, and structures of international student recruitment and enrolment that are characterized by dominating neocolonial values and priorities and to reimagine the practice of recruiting international students and competing in the global international student market by centering primacy of place where “land is not a soulless commodity” to be exploited and profited (Marker, 2019).